A phase I study of nedaplatin, pemetrexed and thoracic intensity-modulated radiotherapy for inoperable stage III lung adenocarcinoma. Issue 1 (December 2016) - Lu, Yiyu; Gu, Weiguang; Deng, Jin; Yang, Hua; Yang, Wen
Abstract Background Concurrent chemotherapy and radiation is the standard treatment for unresectable stage III Lung adenocarcinoma. However, no optimal concurrent chemotherapeutic regimen has been described. This study aimed to assess concurrent pemetrexed, nedaplatin and thoracic intensity-modulated radiotherapy followed by consolidation pemetrexed/nedaplatin for unresectable Stage IIIA/B lung adenocarcinoma. Methods Patients with unresectable stage III lung adenocarcinoma received thoracic intensity-modulated radiotherapy at 60–64 Gy in 30–32 fractions, concurrently with two cycles of 500 mg/m2 pemetrexed, with nedaplatin doses escalating from 60 mg/m2 (level 1) to 70 mg/m2 (level 2) and 80 mg/m2 (level 3). Consolidation consisted of three pemetrexed/nedaplatin (500 mg/m2, 60 mg/m2 ) cycles every 3 weeks after concurrent therapy. The primary objective of the safety was to determine the maximum-tolerated dose (MTD). The secondary endpoints included response rate, PFS and OS. Results Fifteen patients were enrolled, including 3, 6 and 6 individuals in the first, second, and third dose levels, respectively. Three cases of dose-limiting toxicities (grade 3 hepatitis, pneumonitis, and grade 4 thrombocytopenia), including one and two patients at levels 2 and 3, respectively, were observed and resulted in discontinued/delayed treatment. Response rates were 86.7 % (95 % confidence interval [CI], 64.2–97.8 %) and 64.3 % (95 % CI, 38.3–85.4 %) at chemoradiation and treatment completions, respectively. Median OS was 30.0 months (95 % CI, 16.4–43.6 months); 2-year OS was 44.0 % (95 % CI, 18.7–69.2 %). Median PFS was 12.0 months (95 % CI, 6.9–17.0 months), and the 2-year PFS 27.0 % (95 % CI, 4.7–49.3 %). Conclusions Full dose 500 mg/m2 of pemetrexed and nedaplatin 70 mg/m2 could be used safely with thoracic intensity-modulated radiotherapy for inoperable stage III lung adenocarcinoma. Further evaluation of stage III lung adenocarcinoma management is warranted. Trial registration This study was retrospectively registered at Chinese Clinical Trial Registry (ChiCTR-OPN-16008316, April 2016).